Comparative study of physical-chemical features of sacha inchi oil (Plukenetia volubilis l.), olive oil (Olea europaea) and fish oil - Paucar-Menacho, Luz (2015)
Vegetable oils such as sacha inchi (ASI) and oliva (AO) contain mono-unsaturated fatty acids (omega-9) and polyunsaturated (omega-6), and small amounts of omega-3. By contrast, marine oils such as fish oil crude (ACP) are characterized by their high content in omega-3. The objective of this research was to determine and compare the physicochemical of these three oils in order to establish which is the best for food use features. The acidity index, refractive index and specific gravity was determined by AOAC official methods, and the lifetime by the Rancimat method at three temperatures (100 °C, 120 °C and 150 °C), extrapolating the results at 25 °C. The results of the physicochemical characterization indicate that the three oils are significantly different. The acid values in% oleic acid were 1.08, 1.14 and 1.561 for ASI, AO and ACP respectively. The refractive indices (20 °C) were 1.475, 1.469 and 1.481 for ASI, AO and ACP respectively, relative density was 0.9283; 0.9152 and 0.9308 for ASI, AO and ACP respectively. The lifespan for ASI, AO and ACP was 93, 137 and 2 days respectively. The composition of fatty acids in oils from both plant and marine life besides, gives great importance from the nutritional point of view, as they are contained in the oils studied significantly. The results indicate the importance of this type of oils in food.